High-performance liquid chromatography–tandem mass spectrometry for simultaneous determination of 23 antidepressants and active metabolites in human serum and its application in therapeutic drug monitoring - Wang, Jinglong; Wang, Junjie; Zhang, Chenxiao; Li, Guofei (Frontiers in Pharmacology, 2025)
IntroductionThe incidence and mortality rate from depression are increasing year by year, and depression has become the main cause of global health loss and disability. Currently, the treatment of depression mainly relies on drug intervention. However, the vast majority of antidepressants exhibit significant pharmacological variability, resulting in individual differences in steady-state blood drug concentrations even with the same dosing regimen among patients. Therefore, using therapeutic drug monitoring (TDM) to guide the precise use of antidepressants has important clinical significance.MethodsIn this paper, we developed a high-performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) method to study simultaneously TDM and clinical pharmacokinetics of 23 antidepressants and active metabolites: sertraline, escitalopram, fluvoxamine, paroxetine, duloxetine, milnacipran, fluoxetine, venlafaxine, O-desmethylvenlafaxine, mirtazapine, trazodone, bupropion, hydroxybupropione, norfluoxetine, vortioxetine, agomelatine, mianserin, doxepine, desmethyldoxepin, clomipramine, desmethylclomipramine, amitriptyline and nortriptyline hydrochloride. After protein precipitation of serum samples with acetonitrile, the isotope internal standards (ISs), antidepressants and active metabolites were separated using a ZORBAX Eclipse Plus C18 column (50.0 mm × 2.1 mm, 1.7 µm) with water containing 0.1% formic acid and 10 mmol/L ammonium acetate and methanol containing 0.1% formic acid. Validation of the developed method was carried out based on the Chinese Pharmacopoeia guidelines for bioanalytical method validation, including assessment of specificity, calibration curves, carryover, accuracy, crosstalk, precision, stability, recovery, dilution integrity and matrix effect.ResultsThe results showed that a simple, fast, reliable and specific HPLC'MS/MS method was developed and validated, and all the performance characteristics of the method met the requirements, which could be used to study TDM and pharmacokinetics of the above 23 antidepressants and active metabolites.